1984
DOI: 10.1001/archinte.144.8.1687
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytotoxic antibodies in a patient with propylthiouracil-induced agranulocytosis

Abstract: Agranulocytosis developed in a patient who was receiving propylthiouracil. Using a microgranulocytotoxicity assay, serum taken from the patient was shown to be strongly granulocytotoxic when tested against the patients granulocytes and those obtained from two of eight normal subjects. Tests for granulocyte agglutinins and for lymphocytotoxicity were negative. Granulocytotoxic activity decreased as the patient's peripheral granulocyte count recovered. Cytotoxicity was shown to be mediated by a complement-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…There are two possible types of AG pathogenesis: an immune-mediated process and direct or indirect drug intoxication [9]. The existence of circulating complement-dependent IgM antibodies against granulocytes and antibodies against differentiated granulocytes, monocytes, and myeloid/erythroid progenitor cells, for example, has been reported in patients receiving ATD [10,11,12]. The immune-mediated destruction of circulating granulocytes or the suppression of granulopoiesis results in rapid onset of severe neutropenia, whereas AG due to the toxic effects of a drug or its metabolites on bone marrow cells is considered to progress more slowly, taking a couple of weeks.…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible types of AG pathogenesis: an immune-mediated process and direct or indirect drug intoxication [9]. The existence of circulating complement-dependent IgM antibodies against granulocytes and antibodies against differentiated granulocytes, monocytes, and myeloid/erythroid progenitor cells, for example, has been reported in patients receiving ATD [10,11,12]. The immune-mediated destruction of circulating granulocytes or the suppression of granulopoiesis results in rapid onset of severe neutropenia, whereas AG due to the toxic effects of a drug or its metabolites on bone marrow cells is considered to progress more slowly, taking a couple of weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This is inherent to the rarity of the adverse reaction. Case reports were published on all drugs listed as being frequently reported to the DSU in this article, e.g., mianserin, salazosulphapyridine, phenylbutazone, penicillamine, and dipyrone [4], the group of penicillins [5], cimetidine [6], naproxen [7], and the thiouracil derivatives [8,9], but also on drugs that were less frequently reported as a cause, such as clozapine [10][11][12], cephalosporins [13], procainamide [14], dapsone [15,16], paracetamol [17], and ticlopidine [18]. The DSU published case reports and case series on agranulocytosis attributed to aprindine [19,20], spironolactone [21], ticlopidine [22], propylthiouracil [23], pirenzepine [24], trazodone [25], and omeprazole [26], and on leukopenia attributed to mianserin [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, we observed agranulocytosis 3 weeks after initiation of CZ at 10 mg/d, in a patient who had previously been tolerant of MZ for 72 months. As Guffy et al suggested, immunogenic abnormalities that underlie drug sensitivities and induce direct intoxication may be genetic, and some patients may be more susceptible, as in the present case. The most important lesson from this case is that clinicians must remain vigilant for agranulocytosis from antithyroid drugs regardless of treatment duration or dose.…”
Section: Discussionmentioning
confidence: 50%